An augmented Taylor rule for the Federal Reserve's response to asset prices. (2017) - Hafner, Christian M.; Lauwers, Alexandre R.
This paper investigates whether and how the US Federal Reserve has reacted to asset price developments over the period 1979-2011. We examine both the opportunities and limitations of incorporating two asset prices, equity and real estate, into a standard forward-looking and inertial interest rate rule, based on ex-post realised monthly data and taking into account the inherent endogeneity. While the role of house prices is found to be ambiguous due to weak identification, stock prices do represent an important aspect of the Federal Reserve's monetary policy design. Our findings suggest that monetary policymakers did not target stock prices systematically, but rather reacted on few occasions during the full sample period, when misalignments in stock prices were relatively large.